Climate Thermal Requirements for Grain Crops and their Suitability in Iraq - al-Kharbouli, Khalid Ali Atiyah (Al-Adab Journal, 2020)
The needs of each crop differ for the thermal requirements that it needs during the season of its growth, and this variation is the basis of the diversity in agricultural crops. The research relied on the analytical method to find out the suitability of the thermal requirements of grain crops (Wheat, Barley, Yellow Corns , mash) for the eight climate stations (Salah Ad-Din, Mosul, Sulaymaniyah, Khanaqin, Baghdad, Rutba, Samawah, Basra) and for the period (1988 - 2017). The following stations are recorded as the most suitable climatic stations for growing crops according to the optimum temperature limits, two stations (Samawah, Basra) for the crops of Wheat and Barley. Through the optimum temperature data, the autumn loop is the most suitable for the cultivation of Yellow Corn in all stations in question. Spring is the most suitable for growing Mash. The following stations are recorded as the most suitable climatic stations for growing crops according to the optimum thermal limits for two stations (Mosul, Khanaqin) for the Wheat crop, the stations (Mosul, Khanaqin, Rutba) for the Barley and Yellow Corn crops in spring. All stations for the Yellow Corn in autumn, and Mash in spring, and two stations (Salah Al-Din, Sulaymaniyah) for Mash in autumn.